Marketscapes. Market between Culture and Globalization - Rittenhofer, Iris; Nielsen, Martin (HERMES - Journal of Language and Communication in Business, 2009)
What happens to market communication theory (MCT) when it embraces a global business world? MCT’s applications of the ‘global’ turn out to serve “as a magniﬁer” for modernity, when we discuss MCT and its conceptions of the market from the perspective of emergent and dynamic cultural theory. We critically discuss the conception of the market, the relation between communication and market and how globalization is integrated into the ﬁeld. We then interface selected approaches to MCT with cultural approaches to globalization. Finally, we explore and suggest new ways of bringing together market, culture, communication and the global. In the course of these critical discussions, we develop the elements of an alternative conception of the global market as marketscapes. Furthermore, we point to several consequences of our ﬁndings for MCT. MCT has to deal with a global market as a concept, that is a way of perceiving and thinking stakeholder activities in a ‘translocal’, post-national and multidirectional perspective. We conclude by pointing out areas for future MC research.